2020
DOI: 10.1158/1541-7786.mcr-20-0092
|View full text |Cite
|
Sign up to set email alerts
|

The NSD2 p.E1099K Mutation Is Enriched at Relapse and Confers Drug Resistance in a Cell Context–Dependent Manner in Pediatric Acute Lymphoblastic Leukemia

Abstract: The NSD2 p.E1099K (EK) mutation is observed in 10% of acute lymphoblastic leukemia (ALL) samples with enrichment at relapse indicating a role in clonal evolution and drug resistance. To discover mechanisms that mediate clonal expansion, we engineered B-ALL cell lines (Reh, 697) to overexpress wildtype (WT) and EK NSD2, but observed no differences in proliferation, clonal growth, or chemosensitivity. To address whether NSD2 EK acts collaboratively with other pathways, we used shRNAs to knockdown expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…We have identified a hotspot WHSC1 E1099K mutation in two patients with very early relapse and 42,59 Among pediatric tumors, the frequency of WHSC1 mutations is highest in BCP-ALL, especially in ETV6-RUNX1 (20%) and TCF3-PBX1 (15%) ALL subtypes. 42 Therefore, a WHSC1 mutation is unlikely to be a strong risk factor for relapse in these subtypes by itself.…”
Section: A Standard-risk Stratified Patient With On-treatment Relapsementioning
confidence: 96%
“…We have identified a hotspot WHSC1 E1099K mutation in two patients with very early relapse and 42,59 Among pediatric tumors, the frequency of WHSC1 mutations is highest in BCP-ALL, especially in ETV6-RUNX1 (20%) and TCF3-PBX1 (15%) ALL subtypes. 42 Therefore, a WHSC1 mutation is unlikely to be a strong risk factor for relapse in these subtypes by itself.…”
Section: A Standard-risk Stratified Patient With On-treatment Relapsementioning
confidence: 96%
“…NSD2 is involved in the proliferation, apoptosis, and adhesion of MM cells, and the HMT activity of NSD2 is critical for its biological function in tumorigenicity (7). Overexpression or gain-of-function mutation in NSD2 results in drug resistance in multiple cancers (8)(9)(10) and drives endocrine resistance via the reprogramming of metabolism by coordinating pentose phosphate pathway enzymes (11). Although a recent retrospective study showed that t(4;14) translocations are associated with high-risk disease characteristics in patients with MM, they are also associated with better responses to PI-based treatments (12).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, compound 5 with two methoxy groups displayed a good binding affinity to NSD2 PWWP1 domain, with an IC 50 value of 4.44 μM,which is much better than MR837 (4). This encouraged us to synthesize analogs 6 -12.…”
Section: Structure-activity Relationship (Sar) Exploration and Optimization Of Ligandsmentioning
confidence: 98%
“…2 Notably, NSD2 is closely related to accelerated disease progression and rapid relapse in 15-20% of multiple myeloma (MM) harboring the t(4;14) chromosomal translocation with increased levels of H3K36me2, 3 and among the most frequently mutated genes in pediatric cancer genomes, E1099K mutant of NSD2 is hyperactivated in acute lymphoblastic leukemia. 4 Recent studies have revealed that overexpression of NSD2 occurred in several solid tumors including bladder, prostate, glioblastoma and gastrointestinal. 5,6 NSD2 is a multi-domain protein, consists of the SET domain performing the catalytic methylation function and two PWWP (proline-tryptophan-tryptophan-proline) domains.…”
Section: Introductionmentioning
confidence: 99%